Effect of Leadership Style, Work Discipline, and Competency on Job Satisfaction and Performance of Dapodik Operator Employees in Bengkalis District - Sudarno Sudarno; Herma Safitri; Achmad Tavip Junaedi; Amries Rusli Tanjung; Marice Br Hutahuruk (International Conference on Business Management and Accounting, 2023)
This study aims to analyze the effect of leadership style, work discipline and competence on job satisfaction and performance of Dapodik operator employees in the Bengkalis district. This research is quantitative research by distributing questionnaires to respondents. The population in this study were all Dapodik operators in the Bengkalis district. The sampling uses the census method. The sample in this study amounted to 161 respondents. The data analysis technique uses Structural Equation Modelling (SEM) using the SmartPLS application. The results of this study indicate that leadership style does not have a significant effect on job satisfaction, work discipline has a positive and significant effect on job satisfaction, competence has a positive and significant effect on job satisfaction, leadership style has a positive and significant effect on employee performance, work discipline has a positive and significant effect on employee performance, competence has no significant effect on employee performance, and job satisfaction has a positive and significant effect on employee performance.